Exploring Chinese Characteristics in Science Fiction Films: A Case Study of 'Wandering Earth' - Teng, Xu; Desa, Mohd Asyiek Mat (Journal of Ecohumanism, 2024)
Chinese science fiction films were first created in the 1930s, but few outstanding works appeared until the beginning of the 21st century. With the appearance of Wandering Earth in the 2019 Spring Festival, Chinese science fiction films entered a new stage of development.This paper, using the 'Wandering Earth' series as a blueprint for research, first summarizes the development of Chinese science fiction films. Secondly, it focuses on analyzing why 'Wandering Earth' can be considered a genuinely Chinese hard science fiction film.Finally, through the analysis of the Wandering Earth series, we will summarise the future creative direction of Chinese sci-fi films and the experience that can be learnt from it, so as to accumulate creative experience for building domestic sci-fi film IP in the future.